Effect of an age simulation suit on younger adults' gait performance compared to older adults' normal gait - Lauenroth, Andreas; Ioannidis, Anestis E. (Research in gerontological nursing, 2017)
Age simulation suits are used to demonstrate typical physical impairments of older age (e.g., strength and sensory losses) in younger individuals. The purpose of the current study was to describe gait performance in different age groups while wearing an age simulation suit. A total of 178 participants ages 18 to 85 (mean age = 50.4 years, SD = 16.4 years) were assigned according to their age decade to four groups with (ages 18 to 59) and two groups without (ages 60 to 85) the aging suit. Gait performance was measured with a gait analysis system (GAITRite®) while walking at a self-chosen pace. Velocity, step length, step time, and base width were measured. Comparable performance was found for step length and velocity between ages 40 and 49/50 and 59 and ages 60 and 69/70 and 85 (p < 0.05). Results showed no corresponding relationship between step time and base width for all age groups. Simulation training helps younger individuals better understand older adults' perspectives, allowing for more positive interactions.
Gesehen am 25.09.2018